Difference between revisions of "2019 USAMO Problems/Problem 1"

m (Solution)
m (Solution)
 
(4 intermediate revisions by 2 users not shown)
Line 5: Line 5:
  
  
Let <math>f^r(x)</math> denote the result when <math>f</math> is applied to <math>x</math> <math>r</math> times.
+
Let <math>f^r(x)</math> denote the result when <math>f</math> is applied to <math>f^{r-1}(x)</math>, where <math>f^1(x)=f(x)</math>.
 
<math>\hfill \break \hfill \break</math>
 
<math>\hfill \break \hfill \break</math>
 
If <math>f(p)=f(q)</math>, then <math>f^2(p)=f^2(q)</math> and <math>f^{f(p)}(p)=f^{f(q)}(q)</math>
 
If <math>f(p)=f(q)</math>, then <math>f^2(p)=f^2(q)</math> and <math>f^{f(p)}(p)=f^{f(q)}(q)</math>
Line 15: Line 15:
 
<math>\implies p=q</math> since <math>p,q>0</math>.
 
<math>\implies p=q</math> since <math>p,q>0</math>.
  
Therefore, <math>f</math> is injective.
+
Therefore, <math>f</math> is injective. It follows that <math>f^r</math> is also injective.
  
  
Line 23: Line 23:
 
Proof:
 
Proof:
  
<math>f^r(b)=a=f^r(a)</math> which implies <math>b=a</math> by applying injectivity of <math>f</math> <math>r</math> times.
+
<math>f^r(b)=a=f^r(a)</math> which implies <math>b=a</math> by injectivity of <math>f^r</math>.
  
  
Line 35: Line 35:
 
Since <math>k\neq0</math>, <math>f^{f(k)}(k)=k</math>
 
Since <math>k\neq0</math>, <math>f^{f(k)}(k)=k</math>
  
<math>f^m(k)=k</math>
+
<math>\implies f^m(k)=k</math>
  
<math>f^{gcd(m, 2)}=k</math>
+
<math>\implies f^{gcd(m, 2)}(k)=k</math>
  
<math>m=f(k)=k</math>
+
<math>\implies f(k)=k</math>
  
 
This proves Lemma 2.
 
This proves Lemma 2.
Line 48: Line 48:
 
Otherwise, let <math>m</math> be the least counterexample.
 
Otherwise, let <math>m</math> be the least counterexample.
  
Since <math>f^2(m)\cdot f^{f(m)}(m)</math>, either
+
Since <math>f^2(m)\cdot f^{f(m)}(m)=m^2</math>, either
  
<math>(1) f^2(m)=k<m</math>, contradicted by Lemma 1 since <math>k</math> is odd and <math>f(k)=k</math>.
+
<math>(1) f^2(m)=k<m</math>, contradicted by Lemma 1 since <math>k</math> is odd and <math>f^2(k)=k</math>.
  
 
<math>(2) f^{f(m)}(m)=k<m</math>, also contradicted by Lemma 1 by similar logic.
 
<math>(2) f^{f(m)}(m)=k<m</math>, also contradicted by Lemma 1 by similar logic.

Latest revision as of 18:04, 5 April 2021

Problem

Let $\mathbb{N}$ be the set of positive integers. A function $f:\mathbb{N}\to\mathbb{N}$ satisfies the equation \[\underbrace{f(f(\ldots f}_{f(n)\text{ times}}(n)\ldots))=\frac{n^2}{f(f(n))}\]for all positive integers $n$. Given this information, determine all possible values of $f(1000)$.

Solution

Let $f^r(x)$ denote the result when $f$ is applied to $f^{r-1}(x)$, where $f^1(x)=f(x)$. $\hfill \break \hfill \break$ If $f(p)=f(q)$, then $f^2(p)=f^2(q)$ and $f^{f(p)}(p)=f^{f(q)}(q)$

$\implies p^2=f^2(p)\cdot f^{f(p)}(p)=f^2(q)\cdot f^{f(q)}(q)=q^2$

$\implies p=\pm q$

$\implies p=q$ since $p,q>0$.

Therefore, $f$ is injective. It follows that $f^r$ is also injective.


Lemma 1: If $f^r(b)=a$ and $f(a)=a$, then $b=a$.


Proof:

$f^r(b)=a=f^r(a)$ which implies $b=a$ by injectivity of $f^r$.


Lemma 2: If $f^2(m)=f^{f(m)}(m)=m$, and $m$ is odd, then $f(m)=m$.


Proof:

Let $f(m)=k$. Since $f^2(m)=m$, $f(k)=m$. So, $f^2(k)=k$. $\newline f^2(k)\cdot f^{f(k)}(k)=k^2$.

Since $k\neq0$, $f^{f(k)}(k)=k$

$\implies f^m(k)=k$

$\implies f^{gcd(m, 2)}(k)=k$

$\implies f(k)=k$

This proves Lemma 2.


I claim that $f(m)=m$ for all odd $m$.

Otherwise, let $m$ be the least counterexample.

Since $f^2(m)\cdot f^{f(m)}(m)=m^2$, either

$(1) f^2(m)=k<m$, contradicted by Lemma 1 since $k$ is odd and $f^2(k)=k$.

$(2) f^{f(m)}(m)=k<m$, also contradicted by Lemma 1 by similar logic.

$(3) f^2(m)=m$ and $f^{f(m)}(m)=m$, which implies that $f(m)=m$ by Lemma 2. This proves the claim.


By injectivity, $f(1000)$ is not odd. I will prove that $f(1000)$ can be any even number, $x$. Let $f(1000)=x, f(x)=1000$, and $f(k)=k$ for all other $k$. If $n$ is equal to neither $1000$ nor $x$, then $f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2$. This satisfies the given property.

If $n$ is equal to $1000$ or $x$, then $f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2$ since $f(n)$ is even and $f^2(n)=n$. This satisfies the given property.



The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

See also

2019 USAMO (ProblemsResources)
First Problem Followed by
Problem 2
1 2 3 4 5 6
All USAMO Problems and Solutions
Invalid username
Login to AoPS